On multi-frequency systems with impulses - Tkachenko, V.I. (Нелінійні коливання, 1998)
We study exponential dichotomy for a linear quasiperiodic system with impulses. The piecewise smoothness of separatrix manifolds is proved. For nonlinear quasiperiodic impulsive system with linearized system that posseses the property of exponential dichotomy, the conditions for the existence o f discontinuous quasiperiodic solutions are obtained.